The Association of Stress With Anxiety and Depression: Evidence From a Community Health Needs Assessment - Nicole Tournous; Grace Bagwell-Adams (Georgia Southern University, 2016)
Background: Mental illness affects approximately 1 in 5 Americans, making mental health an important area of study for public health. Much research has been conducted on two of the most prevalent mental health disorders, anxiety and depression. However, the association of stress with these disorders, especially specific types of stress (e.g., financial, health, relationship), has been under-studied at the local level. This study aimed to gain insight into the relationship between stress, anxiety, and depression in Athens-Clarke County, Georgia. Methods: Data collected in the 2015 Athens-Clarke County Community Health Needs Assessment were analyzed using linear regression models to explore the association between stress and anxiety and depression. Results:When the data were aggregated, the presence of stress in a respondent's household was associated with a 17.8% (p Conclusions: The results demonstrated that, in Athens-Clarke County, Georgia, stress was significantly and positively associated with both anxiety and depression. Financial, home environment, and neighborhood safety stressors were the strongest predictors of household mental health disorders. These results have implications for public health policy and clinical professionals, including the possibility of tailoring treatment strategies to the types of stress present in a patient's life. Further research is needed to explore this relationship in other communities.